Sequential Pattern Mining Data Transaksi Penjualan Supermarket menggunakan Algoritme Generalized Sequential Pattern - Albert Kurniawan; Ramos Somya (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Online supermarket sales transaction data is a sequence dataset. This data stores purchase transaction data made by customers, so it can be analyzed using Market Basket Analysis (MBA) approach. The problem that is often experienced by supermarkets is the difficulty of implementing the accurate sales strategy to consumers. Based on these problems, this research will analyze the West Superstore supermarket dataset based on the MBA approach. The algorithm used is the Generalized Sequential Pattern (GSP) algorithm, where this algorithm can generate frequent items and sequence patterns, so that the resulting rules can be more accurate. The GSP algorithm in this study is implemented in the Python programming language. The test results show that the output of Python is in accordance with the output of the GSP algorithm calculation. The time required for rule generation in the GSP algorithm also depends on the number of records being used. The more number of sales transactions to be analyzed, it needs longer time in computation. The analysis conducted on the sales dataset at the West Superstore resulted in 391 rules, where these rules can be used by supermarkets to implement their sales strategies.